The aerodynamic effects on a cornering Ahmed body. Issue 154 (July 2016) - Keogh, James; Barber, Tracie; Diasinos, Sammy; Doig, Graham
Abstract: As a vehicle travels through a corner, the flowfield observed from the vehicle׳s frame of reference becomes curved. This condition results in the relative flow angle and freestream velocity changing both across the width and along the length of the body. Wall-resolved Large Eddy Simulations were used to simulate a simple vehicle shape through three different radii corners. The variable flow angle and acceleration affected the pressure distribution along either side of the body and caused an increase in the size of the outboard C-pillar vortex, and an inboard decrease. Furthermore, an outboard extension of the separation bubble at the bluff trailing face resulted in a gentler downwash angle off the backlight surface, with the opposite occurring inboard. At a Reynolds number of 1.7×10 6, a 19.2% increase in aerodynamic drag occurred for a five car-length radius corner when compared to the straight-line condition. In addition, a yawing moment acted against the rotation of the body through the corner, and a side force acted towards the centre of the corner. An exponential trend related the curvature of a vehicle׳s path to the increase in aerodynamic drag, with a linearity exhibited for the increase in yawing moment and side force. Highlights: Cornering affected the aerodynamic characteristics of a simple vehicle shape. Large Eddy Simulations were used to model three different radius corners. C-pillar vortices and separated flow regions become asymmetric. Drag coefficient increased as corner radius decreased.